2007
DOI: 10.5172/conu.2007.24.2.189
|View full text |Cite
|
Sign up to set email alerts
|

Human resource management strategies for the retention of nurses in acute care settings in hospitals in Australia

Abstract: It is paramount that there is an adequate nursing workforce supply for now and in the future, to achieve equitable and quality health outcomes and consumer access to healthcare, regardless of geographic location. Nursing forms the largest body of employees in the health care system, spanning all segments of care. A shortage of nurses, particularly in the acute care settings in hospitals, jeopardizes the provision of quality health care to consumers. This article provides a literature review of Australian State… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 10 publications
(15 reference statements)
0
36
0
1
Order By: Relevance
“…Dykes (2011) agreed that some students may experience lasting effects from early adverse experiences that may interfere with healthy and effective practice. When students are not sufficiently prepared to manage intense emotions that may be triggered, they may develop coping strategies that diminish both job performance and longevity in the profession (Hogan, Moxham, & Dwyer, 2007). Given the complex and potentially competing requirements of gatekeeping and promoting social justice for social work educators, it is not surprising that professional training programs struggle with how to best serve students who carry such difficult experiences with them into their professional training.…”
Section: Meaning For Social Work Educationmentioning
confidence: 96%
“…Dykes (2011) agreed that some students may experience lasting effects from early adverse experiences that may interfere with healthy and effective practice. When students are not sufficiently prepared to manage intense emotions that may be triggered, they may develop coping strategies that diminish both job performance and longevity in the profession (Hogan, Moxham, & Dwyer, 2007). Given the complex and potentially competing requirements of gatekeeping and promoting social justice for social work educators, it is not surprising that professional training programs struggle with how to best serve students who carry such difficult experiences with them into their professional training.…”
Section: Meaning For Social Work Educationmentioning
confidence: 96%
“…More than 90% of surveyed nurses have observed raucous behaviour. 12 Job dissatisfaction has been identified as a major contributing factor to the current problems of recruiting and retaining nurses. A recent Federation of Nurses and Health Professionals Survey showed that over the past two years, half of currently employed RNs considered leaving the patient-care field for reasons other than retirement.…”
Section: Future and Present Supply Issuesmentioning
confidence: 99%
“…The job attributes are based on the literature describing job characteristics associated with nurse retention (Naude and McCabe, 2005;Hayes et al, 2006;Hogan et al, 2007). The attributes and levels are presented in Table 1; the experiment includes 12 attributes, 11 with two levels and one (salary) with four levels.…”
Section: The Choice Experimentsmentioning
confidence: 99%